EDUKASI PRAKTIK PIJAT OKSITOSIN SEBAGAI UPAYA MENINGKATKAN PRODUKSI ASI - Lubis, Dinni Randayani; Anggraeni, Legina (Jurnal Pengabdian Masyarakat AbdiMas, 2024)
Low oxytocin levels can trigger various problems, such as difficulty breastfeeding, postpartum depression, and difficulty bonding with the baby, which will have an impact on reducing breastfeeding. Lack of breastfeeding for babies can increase the risk of babies experiencing stunting. Efforts to increase oxytocin levels are made to support the health of mothers and babies. The coverage of exclusive breastfeeding in DKI Jakarta for six-month-old babies is 65.63%. One way to overcome irregularities in breast milk production is by doing an oxytocin massage. Oxytocin massage is a safe and effective massage technique to stimulate the production of the hormone oxytocin. The aim of this community service activity is to provide education to mothers of babies about the practice of oxytocin massage, which can help increase breast milk production in babies. The method used is education about oxytocin massage through counseling and the practice of oxytocin massage. This activity was attended by 30 participants, consisting of mothers with babies 0–6 months and health cadres. This activity will be carried out in the Cililitan area, Kramat Jati District, East Jakarta, in 2023. The results of the community service activities that have been carried out are increasing participants' knowledge about the effectiveness of oxytocin massage.